Java how to program, late objects - Deitel, Paul J.; Deitel, Harvey M. (Pearson Education Limited, 2020)
The Deitels' groundbreaking How to Program series offers unparalleled breadth and depth of programming fundamentals, object-oriented programming concepts and intermediate-level topics for further study. Java How to Program, Late Objects, 11th Edition, presents leading-edge computing technologies using the Deitel signature live-code approach, which demonstrates concepts in hundreds of complete working programs. The 11th Edition presents updated coverage of Java SE 8 and new Java SE 9 capabilities, including JShell, the Java Module System, and other key Java 9 topics.